Business Digitalism: Digital Transformation, Strategy, and Customer Engagement in Contemporary Enterprises - Gusev Laroslav (Lembaga Pengembangan Kinerja Dosen, 2026)
This study examines the transformative impact of business digitalization on contemporary enterprises, focusing on how digital technologies reshape organizational structures, cultures, and value creation processes. In the era of the Fourth Industrial Revolution, companies increasingly rely on artificial intelligence, big data, automation, and cloud computing to enhance efficiency and remain competitive. Yet, the transition to digital systems introduces challenges such as cybersecurity risks, data management complexities, and organizational resistance to change. Drawing on the insights of Adam Smith and Marshall McLuhan, this research connects classical economic theories of labor division and competition with modern digital innovation, while also highlighting how digital media alter business models and customer engagement. Using a qualitative research design supported by an extensive literature review, the study identifies key themes including decentralized organizational structures, innovation-driven cultures, enhanced personalization, and the emergence of new digital value streams. The findings indicate that successful digital transformation requires a clear strategic vision, agile leadership, investment in digital talent, and robust cybersecurity measures. Overall, this research emphasizes that while digitalization offers immense opportunities, its benefits can only be fully realized when organizations address its challenges proactively and adapt continuously to technological change.